Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1080/14786419.2022.2056182
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids from the rhizomes of Homalomena pendula and their anti-inflammatory activities

Abstract: Sixteen sesquiterpenoids including two new ones, homalolides AB (1-2), were firstly isolated from the methanolic extract of the rhizomes of Homalomena pendula collected in Vietnam. The structures and relative stereochemistry of new compounds were elucidated by 1D-/2D-NMR, IR, UV and HRESIMS analyses. The GCMS experiment demonstrated that homalolide A ( 1) is an artifact due to the methylation during methanolic extraction process.All isolates (1-16) were tested for their inhibitory activities against lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, the presence of homalolide A may have been an artifact due to methylation during the methanolic extraction process. 24 α-Cadinol, 33 homalomenol C, 34 homalomenol A, bullatantriol, and 1β,4β,7α-trihydroxyeudesmane, 35 spathulenol, 36 teucmosin, 37 oplopanone, 38 and 1α,4β,5α,6β,7βH,10β-4,10-epoxy-6-guainol 39 have also been isolated from other Homalomena species. Osteoblasts produce ALP in the bone and play an important role in bone growth and quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of homalolide A may have been an artifact due to methylation during the methanolic extraction process. 24 α-Cadinol, 33 homalomenol C, 34 homalomenol A, bullatantriol, and 1β,4β,7α-trihydroxyeudesmane, 35 spathulenol, 36 teucmosin, 37 oplopanone, 38 and 1α,4β,5α,6β,7βH,10β-4,10-epoxy-6-guainol 39 have also been isolated from other Homalomena species. Osteoblasts produce ALP in the bone and play an important role in bone growth and quality.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Earlier research demonstrated its anti-inflammatory properties. 24 In this work, we determined the chemical composition of the volatile oil by preparing an n -hexane extract of the plant, as well as its anti-osteoporotic characteristics associated with alkaline phosphatase (ALP) activity, collagen content, and mineralization. Our results show that H. gigantea stimulates osteoblast differentiation and proliferation, thus enhancing bone growth.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Investigating the composition and biological activities of H cochinchinensis rhizomes is important for clarifying the role of this plant in folk medicine. As part of an ongoing investigation of bioactive metabolites from plants of the Homalomena genus collected in Vietnam, [8][9][10] we report herein the composition of volatile components from H cochinchinensis rhizomes. We also investigated the extract's cytotoxic activity against SK-LU-1 (human lung adenocarcinoma), HepG2 (human hepatocellular carcinoma), and MCF7 (human breast cancer) cell lines; its inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 cells; and its capacity for acetylcholinesterase (AChE) inhibition.…”
Section: Introductionmentioning
confidence: 99%